Fluid Design in Contemporary Architecture: Balancing Design and Application (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The design has a direct impact on our emotions and psychological well-being, making it crucial to achieve a seamless experience, both in terms of design and movement inside a given space. Colour balance is a fundamental design element because it conveys the ambiance and evokes a sense of relaxation, all while preserving a luxurious character.With the introduction of computer programmes and the use of contemporary techniques in architecture and interior design, fluid architecture emerged as a new trend in design and technology. Prominent practitioners of this movement include Frank Geery and Zaha Hadid. It is believed that technology can be achieved through the design process, which has evolved into a means by which the designer can generate ideas for an interior architecture marked by fluidity and unexpected engineering that draws inspiration from nature and is unconstrained by conventional design and structural constraints. Both energetic and geometrical.When planning a building's exterior and interior, as well as how it interacts with its environment, architects and designers must take streamlined design into account. The buildings are stable, but they nevertheless gain an advantage from the winds and air circulation around them.The introduction of computers and their programmers, along with the use of contemporary technologies in interior design, furniture, and architecture, exposed many early architects, including Frank Gehry and Zaha Hadid, to technology in fluid architecture. The purpose of this work is to provide an interior architectural style that is both free from conventional design and construction constraints and defined by a fluidity of form and unexpected geometry drawn from nature. The article begins with a short introduction to fluid design before moving on to discuss its characteristics and features, generic design, layout, and actual applications. Lastly, we highlight a few opportunities and threats found in the vast fluid architecture design literature review.